An expert consensus on the most effective components of cognitive behavioural therapy for adults with depression: a modified Delphi study. Issue 3 (3rd May 2020) - Taylor, Abigail; Tallon, Deborah; Kessler, David; Peters, Tim J.; Shafran, Roz; Williams, Chris; Wiles, Nicola
ABSTRACT: Designing new approaches to delivering cognitive behavioural therapy (CBT) requires an understanding of the key components. This study aimed to establish an expert consensus on the effective components of CBT for depressed adults. An international panel of 120 CBT experts was invited to participate in a modified Delphi study. Thirty-two experts participated in round 1; 21 also provided data in round 2. In round 1, experts rated the effectiveness of 35 content and process components. A priori rules identified components carried forward to round 2, in which experts re-rated items and final consensus items were identified. Consensus was achieved for nine content components (ensuring understanding; developing and maintaining a good therapeutic alliance; explaining the rationale for CBT; eliciting feedback; identifying and challenging avoidant behaviour; activity monitoring; undertaking an initial assessment; relapse prevention methods; homework assignments); and three process components (ensuring therapist competence; scheduling sessions flexibly; scheduling sessions for 45–60 mins). Five of the twelve components identified were generic therapeutic competences rather than specific CBT items. There was less agreement about the effectiveness of cognitive components of CBT. This is an important first step in the development of novel approaches to delivering CBT that may increase access to treatment for patients.